Diagnostic Clusters in Shoulder Conditions - Monga, Puneet; Funk, Lennard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book serves as a definitive guide to diagnosing shoulder conditions for trainees, general practitioners, physiotherapists, orthopaedic surgeons and radiologists with an interest in shoulder pathology. It comes at a time when the knowledge regarding shoulder conditions has vastly improved, with the shoulder sub-speciality growing at a rapid pace in terms of practitioner numbers, procedures and evidence base. It is unclear, in most circumstances, which single clinical test or indeed radiological investigation is the best for diagnosing a particular condition. In fact, the diagnosis of a particular shoulder condition rests on the four sub-components of clinical history, conventional examination, special tests and radiological investigations. It is often the case that all these sub-components are to be used in conjunction with each other as (3z(Bclusters(3y (Brather than in isolation. This forms the basis of the cluster approach, which is the key concept for the title and content of this book. This book presents a practical guide for diagnosis, written by a select group of surgeons and physiotherapists with a special interest in shoulder pathologies, who have painstakingly extracted these relevant clusters for each shoulder conditions from clinical experience and published work.s
Part 1. Rationale of Diagnostic Clusters -- Clinical History -- The Conventional: Look Feel & Move -- Special tests -- Radiological Techniques -- Choosing the Right Cluster -- Part 2. Shoulder Pain Clusters -- Impingement -- Supraspinatus -- Infraspinatus -- Subscapularis -- Teres Minor -- LHB tendinitis -- SLAP tear -- AC joint -- GH arthritis -- Internal Impingement -- Coracoid Impingement -- Scapular Dyskinesia -- Part 3: Shoulder Instability Clusters -- Anterior Instability -- Posterior Instability -- Inferior Laxity -- SC instability -- AC joint instability -- Part 4: Neurology Clusters -- Cervical disc disease -- Axillary Nerve palsy -- Supraspinatus Nerve Palsy -- Brachial Plexus palsy -- Part 5: Radiological clusters -- RC disease -- Instability -- Fractures -- Tumours -- Shoulder Surgery.
Keywords: Medicine; Orthopedics; Medicine & Public Health; Orthopedics